KLASIFIKASI JENIS PENUTUPAN LAHAN MENGGUNAKAN CITRA LANDSAT 8 DI KAWASAN CAGAR ALAM GUNUNG DAKO KELURAHAN TUWELEY KECAMATAN BAOLAN KABUPATEN TOLI TOLI PROVINSI SULAWESI TENGAH - Rusmiyati, Rusmiyati; Akhbar, Akhbar; Arianingsih, Ida (Universitas Tadulako, 2015)
The criteria of stating an area to become the natural conservation area is stand in national constitution no. 5 year 1990 and in goverment rule no. 28 year 2011 about natural conservasion management. Based on this rule, there are two kinds of natural conservation areas, namely: natural reservation area and wildlife conservation area. These areas are used only for science and education . when the natural reservation area disturbed by the number of the population which getting bigger each day. The function of the land is also multiplied in use. This condition leads to the decreasing number of the natural reservation area itself. By this phenomenon, the surrounding villagers started to use the reservation area as an alternative to fulfill their daily needs and indirectly lead to the change of area coverage in Tuweley sub district, Baolan district, Toli-Toli regency. The objective of this research was to find out the wide and kind of area coverage in Gunung Dako natural reservation in Tuweley sub district, Baolan district, Toli-toli regency, Central Sulawesi Province by using the overview from Landsat 8 Version 2013. The method used in this research was overview correction. This overview correction used radiometric which cover the sharpening process to make the exposure usable. The sharpening exposure process was done in order to raise the expsure interpretation by sharpening the contrast of an object. The data from Landsat 8 version 2013 then interpreted digitally to classify the area coverage by its color and pattern from the score of spectrum object exposure using Arc. Gis software 10.1 version. This research was conducted in Gunung dako natural reservation in Tuweley sub district, Baolan district, Toli-Toli regency Central Sulawesi Province. This research was conducted in three months started from March to Juni 2014. The record from Landsat 8 version 2013 with band composite 654 was quite good in providing clear area coverage clasification since it could provide bright colour and clear pattern of the area. From the result of Landsat 8, there were 6 kind of area coverage clasification of Gunung Dako natural reservation in Tuweley sub district, Baolan district, Toli-Toli regency, Central Sulawesi Province as follows: the wide of primary forest is 2.757,46 ha (73,19%), the wide of farm is 1,69 ha (0,044%), the wide of the open area is 1,24 ha (0,032%). Furthermore, the wide of bed is 1,43 ha (0,037%), the wide of stream is 2,09 ha (0,055%) and the wide of cloud is 1003,631 ha (26,64%). Keywords: Area Coverage,Landsat 8View, Gunung Dako, and Tuweley Subdistrict.